VD_FINDINFO HC / 2014 / 341 vom 8. April 2014 - VD Tribunal cantonal (2014)
ABUS DE DROIT, OBLIGATION D'ENTRETIEN, RELATIONS PERSONNELLES | 163 CC, 176 al. 1 CC, 176 al. 3 CC, 273 CC, 274 al. 2 CC, 308 al. 1 let. b CPC (CH), 312 al. 1 CPC (CH)